2004
DOI: 10.1348/1359107041557039
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive‐behavioural rehabilitation programme for patients with an implanted cardioverter defibrillator: A pilot study

Abstract: A comprehensive 12-week CR programme that incorporated both psychological and exercise-based components significantly reduced anxiety and depression and improved quality of life of ICD patients. It is not clear if these benefits are sustained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(126 citation statements)
references
References 12 publications
(13 reference statements)
5
117
1
3
Order By: Relevance
“…There was no significant effect on the number of ICD shocks that were received. Frizelle et al, 163 using an intervention and wait-list control group design, tested the effects of 6 weekly 2-hour CBT sessions in 21 secondary prevention patients. Subjects crossed over to the other group after 6 weeks, and outcomes were compared at 12 weeks.…”
Section: Overview Of Specific Psychological and Educational Interventmentioning
confidence: 99%
“…There was no significant effect on the number of ICD shocks that were received. Frizelle et al, 163 using an intervention and wait-list control group design, tested the effects of 6 weekly 2-hour CBT sessions in 21 secondary prevention patients. Subjects crossed over to the other group after 6 weeks, and outcomes were compared at 12 weeks.…”
Section: Overview Of Specific Psychological and Educational Interventmentioning
confidence: 99%
“…Finally, exercise training as part of a comprehensive cardiac rehabilitation program has reduced anxiety and depression and improved quality of life in ICD patients. 16,17 However, these studies enrolled older adults (mean age, late 50s), and the largest one specifically excluded patients with genetic arrhythmias, 13 so it remains to be seen whether similar interventions will be equally feasible and successful at reducing anxiety and improving quality of life in ICD patients with ARVC and other inherited cardiac diseases.…”
Section: Article See P 18mentioning
confidence: 99%
“…Kohn et al 11 demonstrated cognitive-behavioral therapy (CBT) which included psychoeducation, stress management, and the examination of distorted thoughts about ICD-specific concerns; it was associated with significantly less depression, anxiety, and adjustment difficulties compared with controls at 9-month followup. More recently, Frizelle et al 12 demonstrated the effectiveness of a CBT intervention in reducing anxiety and depressive symptoms and improving quality of life in patients with ICD in the cardiac rehabilitation setting over a period of 6 weeks. Collectively, these results suggest that psychosocial interventions, especially those including a cognitive or cognitive-behavioral approach, may alleviate negative emotions and improve well-being in patients with ICDs.…”
Section: Patient Factors In Cardiac Researchmentioning
confidence: 99%